The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1590/s1516-89131999000400009
|View full text |Cite
|
Sign up to set email alerts
|

Diet and dietary overlap of three sympatric fish species in lakes of the upper Paraná River floodplain

Abstract: For a dietary study, specimens of Astyanax bimaculatus, Astyanax schubarti, and Moenkhausia intermedia were caught monthly with seines-nets in six lakes (Pau Veio, Porto Rico, Três Amigos, Mutum, Pontal, and Canal do Meio), on the floodplain of the Upper Paraná River, from March 1992 through February 1993. We analyzed stomach contents of 599 A. bimaculatus, 293 A. schubarti, and 394 M. intermedia, by the Occurrence and Points methods, combined in the Alimentary Index (AI). This analysis revealed that these spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…as well as spatial and seasonal modifications in the composition of its diet. This was observed in other characin species (Luz & Okada, 1999;Mazzoni & Rezende, 2003).…”
Section: Discussionsupporting
confidence: 79%
“…as well as spatial and seasonal modifications in the composition of its diet. This was observed in other characin species (Luz & Okada, 1999;Mazzoni & Rezende, 2003).…”
Section: Discussionsupporting
confidence: 79%
“…Several authors have indicated considerable ecological diversity in A. altiparanae , both in diet (Luz & Okada, 1999) and behaviour (Suzuki & Orsi, 2008). The deep divergence observed among sympatric haplotypes, however, indicates that two biological species might be currently recognized by the same name, which could partially explain its ecological versatility.…”
mentioning
confidence: 99%
“…To better understand the role of the simultaneous biological interactions that affect the early establishment phase of H. verticillata invasions, we conducted a mesocosm experiment that assessed the individual and combined effects of three aquatic species that damage H. verticillata in different ways and represent some of the possible biotic interactions found in lakes. Based on our prior observations (see also Langeland, 1996;Luz & Okada, 1999;Fellerhoff, 2002 (Sousa, 2011), probably from a single introduction of a dioecious female (Sousa, 2011). Despite the high degree of phenotypic plasticity in H. verticillata, the plant has not been able to establish stable populations in floodplain lakes (Sousa, 2011;Sousa et al, 2009), which are inhabited by the resistance-promoting species that we considered in this study (M. forestii, Pomacea spp.…”
Section: Introductionmentioning
confidence: 78%
“…Based on our prior observations (see also Langeland, 1996;Luz & Okada, 1999;Fellerhoff, 2002 (Sousa, 2011), probably from a single introduction of a dioecious female (Sousa, 2011). Based on our prior observations (see also Langeland, 1996;Luz & Okada, 1999;Fellerhoff, 2002 (Sousa, 2011), probably from a single introduction of a dioecious female (Sousa, 2011).…”
Section: Introductionmentioning
confidence: 86%